2017
DOI: 10.1371/journal.ppat.1006000
|View full text |Cite
|
Sign up to set email alerts
|

Social and Genetic Networks of HIV-1 Transmission in New York City

Abstract: BackgroundSexually transmitted infections spread across contact networks. Partner elicitation and notification are commonly used public health tools to identify, notify, and offer testing to persons linked in these contact networks. For HIV-1, a rapidly evolving pathogen with low per-contact transmission rates, viral genetic sequences are an additional source of data that can be used to infer or refine transmission networks.Methods and FindingsThe New York City Department of Health and Mental Hygiene interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
173
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 178 publications
(183 citation statements)
references
References 49 publications
9
173
1
Order By: Relevance
“…Owing to incomplete sampling or significant modularity of contact networks, transmission networks identified among persons at high-risk of infection are frequently organized into several components and unlinked nodes (Wertheim et al, 2017; Wertheim et al, 2014), similar to the ITN used in this study (Fig. 2).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Owing to incomplete sampling or significant modularity of contact networks, transmission networks identified among persons at high-risk of infection are frequently organized into several components and unlinked nodes (Wertheim et al, 2017; Wertheim et al, 2014), similar to the ITN used in this study (Fig. 2).…”
Section: Discussionmentioning
confidence: 98%
“…HCV spread among high-risk populations such as PWID and men-who-have-sex-with-men (MSM) is facilitated by tight contact networks (Rolls et al, 2013), which can be modeled as transmission networks identified using genetic approaches (Wertheim et al, 2017). However, transmission networks are not frequently available to guide PHI, prompting the use of other approaches like an acquaintance network (Chami et al, 2017; Hellard et al, 2014) to estimate indirectly the underlying contact network structure.…”
Section: Discussionmentioning
confidence: 99%
“…All pairwise distances were computed and a putative linkage between two individuals was considered whenever their pol sequences were ≤0.015 substitutions/site divergent (TN93 substitution model) (3133). When calculating pairwise genetic distance, all nucleotide ambiguities were resolved and only sequences with less than 1.5% ambiguities were retained (34). Problematic sequences, including those closely related to HXB2 and NL4-3, which could be deemed as possible contaminants, were flagged and repeated based on phylogenetic analyses performed on a monthly basis as an internal laboratory control.…”
Section: Methodsmentioning
confidence: 99%
“…Clusters comprised of only two linked nodes were identified as dyads. This approach will detect clusters of recent transmission in which the clustering viruses are genetically similar, implying a direct or indirect epidemiological connection (34). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation